O ensino e a aprendizagem da progressão aritmética através da resolução de problemas - Vargas, Claudia Vieira de (2019)
The motivation for the development of this research stems from concerns and observations about the teaching and learning of arithmetic progression. Usually in schools, the approach to this content does not favor understanding, because use and memorization of formulas are emphasized. On the other hand, there are studies indicating good results obtained with the use of problem solving in mathematics education. The objective of this research is to investigate how the methodology of teaching-learning-evaluation of Mathematics through problem-solving, contributes to the teaching on arithmetic progression in a 1st year high school class. São José Institute was the school where this work was developed and is the school where researcher works as a teacher. The data collect was developed in eight meetings and used the Methodology of Teaching-Learning-Assessment of Mathematics as a theoretical support, through the Problem Solving proposed by Allevato and Onuchic (2014). Problems were planned and applied that would allow the construction and formalization of such content. The research had a qualitative approach, using three instruments in the data collection: questionnaire, observation and documentary analysis. The documents reviewed were, especially the resolutions produced by students during the meetings. And the records of the observations were as follows: field diary, audio recordings, and photographs. With the analysis and discussion of the collected data we noticed that the problems developed inserted the students in the process of constructing the concepts, making them producers of own knowledge, because the strategies used in the resolution of the problems led to the reflection, contributing to the recognition, systematization and formalization of mathematical concepts. Thus, the use of problem solving as a teaching methodology, favored from less abstract manner to the approach of the student with the content studied. This methodology has become an important strategy that generated great interest and motivation on the part of students, developing a favorable environment for the learning of Mathematics. We hope, with this research, to contribute with suggestions and strategies of teaching capable of breaking with the memorization of formulas, which little contributes to the formation of our students, in particular, in the teaching of Arithmetic Progression.